2012
DOI: 10.4103/1947-2714.92899
|View full text |Cite
|
Sign up to set email alerts
|

Medicine vendors: Self-medication practices and medicine knowledge

Abstract: Background:Medicine vendors fill the gap created by inadequate skilled professionals required for medicine procurement, storage, and distribution in developing countries.Aim:To evaluate self-medication practice and medicine knowledge among medicine vendors and to determine if a relationship exists between both.Materials and Methods:A descriptive, cross-sectional study was conducted, using a pretested questionnaire on 236 medicine vendors in Jos, Nigeria, sampled through a two-stage stratified design. Data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 10 publications
6
31
3
3
Order By: Relevance
“…Analgesics/antipyretics were the most commonly used self‐medications among OTC products, which was in agreement with previous studies . This can be attributed to the common use of such drugs in treating minor and uncomplicated illnesses such as fever, headache, and pain . Beside analgesics, supplements were the second mostly used OTC products, which is similar to what was reported in different countries such as Malaysia and the United States .…”
Section: Discussionsupporting
confidence: 90%
“…Analgesics/antipyretics were the most commonly used self‐medications among OTC products, which was in agreement with previous studies . This can be attributed to the common use of such drugs in treating minor and uncomplicated illnesses such as fever, headache, and pain . Beside analgesics, supplements were the second mostly used OTC products, which is similar to what was reported in different countries such as Malaysia and the United States .…”
Section: Discussionsupporting
confidence: 90%
“…This is because such drugs are applied to treat uncomplicated common illness such as headache, fever and pain. This confirms that analgesics/antipyretics are the commonly used over-the-counter medications for self-medication [16]. Over-the-counter drugs, selected and utilized properly, can be highly effective in ameliorating symptoms while avoiding trivial or unnecessary physician office visits and more expensive, but not always more effective, prescription drug use [7].…”
Section: Discussionmentioning
confidence: 59%
“…16 In a study conducted by Asa auta et al, the prevalence of self medication among medicine vendors was 75.4%. 17 Another study conducted among the health workers in tertiary hospital at Ondo State, Nigeria reported a prevalence of 73%. 18 Demographic variable such as education status, socioeconomic status, gender and age also affect the status of self medication, with Selfmedication being more in advanced education, in middle income earners, female and lesser than 40 years of age.…”
Section: Discussionmentioning
confidence: 99%